Strain, Anger, and Violent Behavior of South Korean Adolescents - Lee, Wonki (Journal of interpersonal violence, 2024)
Although general strain theory (GST) highlights the mediating role of anger between strain and violent behavior, the extant body of literature has been criticized for lack of rigorous testing of the mediating role of anger and lack of application in different cultural contexts. To cover this research gap, the current study investigated the mediating effect of anger between primary sources of strain of South Korean adolescents (i.e., parental abuse, academic-related strain, and negative relations to teacher) and violent behavior. Using structural equation modeling based on a nationally representative longitudinal dataset (n = 3,120), this study found a significant mediating role of anger in connecting strain and violent behavior of South Korean adolescents. Results from the present study support the main proposition of the GST on the mediating role of anger and its applicability in a cross-cultural context. Theoretical and practical implications are discussed.